The Effectiveness of Creative Problem Solving (CPS) Learning Model on Divergent Thinking Skills - Tri Murwaningsih; Muna Fauziah (International Journal of Science and Applied Science: Conference Series, 2020)
This study has a goal to determine the effectiveness of the CPS learning process in thematic learning and the effectiveness of CPS on students' divergent thinking skills. The exploratory sequential mixed method was used in this study. The study participants were 184 fifth-grade students at public elementary schools in Laweyan District. Test instruments, observation sheets, and documentation were used to collect research data. The content and construct validations were used to test the validity of the test instrument, while the observation sheet and documentation were only tested for their content validity. This study went through two stages of data analysis, namely quantitative tests (normality, homogeneity, balance, hypothesis, and post-ANOVA tests) and qualitative analysis using interactive analysis methods through data reduction, data display, and conclusion drawing. The results of the study describe the calculation of the hypothesis test with an F obs value of 18.23 which is higher than the F table value of 3.02 with a significance level of 0.05. The average score of students who learn using the CPS model is 69.36 while students who use the DI model obtain an average score of 63.43. Students demonstrate every indicator of divergent thinking skills (fluency, flexibility, originality, and elaboration) during the learning process with the CPS model. Therefore, it can be concluded that the CPS learning model is more effective than DI to improve students' divergent thinking skills. The results of this study can be applied to improve the divergent thinking skills of elementary school students.